2020
DOI: 10.1101/2020.01.16.909606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biases and Blind-Spots in Genome-Wide CRISPR Knockout Screens

Abstract: It is widely accepted that pooled library CRISPR knockout screens offer greater sensitivity and specificity than prior technologies in detecting genes whose disruption leads to fitness defects, a critical step in identifying candidate cancer targets. However, the assumption that CRISPR 5 screens are saturating has been largely untested. Through integrated analysis of screen data in cancer cell lines generated by the Cancer Dependency Map, we show that a typical CRISPR screen has a ~20% false negative rate, bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Inhibition of a protein is also intrinsically different than a knockout, as observed for PARP inhibitors whose activity is mediated through formation of cytotoxic PARP‐DNA complexes, whereas PARP knockout has little or no effect on cell fitness (Gill et al , ; Murai & Pommier, ; Antolin et al , ) (Fig EV3H). Similarly, redundancy of gene paralogs when using single‐gene CRISPR knockout may confound comparisons with drugs that target multiple paralogs (preprint: Dede et al , ). Thus, although the reasons may vary for each drug, the absence of an association between drug sensitivity and CRISPR loss‐of‐function effects could warrant further investigation into drug mechanism‐of‐action to understand possible underlying factors, such as low potency, alternative molecular mechanisms, or polypharmacology.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of a protein is also intrinsically different than a knockout, as observed for PARP inhibitors whose activity is mediated through formation of cytotoxic PARP‐DNA complexes, whereas PARP knockout has little or no effect on cell fitness (Gill et al , ; Murai & Pommier, ; Antolin et al , ) (Fig EV3H). Similarly, redundancy of gene paralogs when using single‐gene CRISPR knockout may confound comparisons with drugs that target multiple paralogs (preprint: Dede et al , ). Thus, although the reasons may vary for each drug, the absence of an association between drug sensitivity and CRISPR loss‐of‐function effects could warrant further investigation into drug mechanism‐of‐action to understand possible underlying factors, such as low potency, alternative molecular mechanisms, or polypharmacology.…”
Section: Resultsmentioning
confidence: 99%
“…Our core gene analysis captured almost all genes identified by ADaM (Behan et al , 2019), and identified 195 new core essential genes involved mainly in previously known‐to‐be‐essential cellular processes, but also added an additional process of COP9 signalosome complex to these. The core analysis from CEN‐tools could also capture all but 11 genes from the very recent core gene analysis from Dede et al (preprint: Dede et al, 2020), which used the same data sets as in this study (Appendix Fig S9). As the essentiality measured from genetic screens not only captures genes whose loss causes cell death, but also genes whose loss results in slower proliferation of the cells, the day the experiments were performed will affect the identification of the genes essential for proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The paralog pairs which were both constitutively expressed gene lists were identified and were binned according to different thresholds for percent sequence identity from a range of 10-95%. For each bin, the percentage of constitutively expressed never-essential genes with paralogs and the percentage of common essential genes (defined in [41]) with paralogs were calculated and their distributions were plotted. For downstream analysis, always expressed paralog pair lists were generated for each sequence identity threshold.…”
Section: Paralogsmentioning
confidence: 99%